Coping with School Burnout - İsmail Seçer; Selim Gündoğan (Psikiyatride Güncel Yaklaşımlar, 2022)
School burnout has been the subject of research as the form of professional burnout seen in students who continue their education life. In the relevant literature, it is seen that the factors that increase or decrease school burnout and the negativities caused by school burnout are examined. However, it is noteworthy that the issue of coping with school burnout, which is a common problem that almost every student experiences at certain times in their education life, is not addressed. In this review study, the concept of school burnout was first explained, and then the concepts of coping and coping with school burnout were discussed.